The Influence of Leadership Style, Work Commitment and Employee Attachment on Employee Performance at PT Ingco - Lyra Aulia; M. Chaerul Rizky; Aswan Waruwu (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the influence of leadership style, work commitment, and employee attachment on employee performance at PT INGCO. Employee performance is a key factor that determines the success of an organization in the face of increasingly competitive business competition. This type of research is quantitative research with a causal associative approach.  The population in this study is all employees of PT INGCO which currently amounts to 85 employees, and the entire population is used as a research sample (saturated sampling). The data collection method used a questionnaire with a Likert scale, and the data analysis technique used was multiple linear regression analysis with the help of SPSS software. The results of the study showed that: (1) Leadership style had a positive and significant effect on employee performance with a calculated t value of 4.151 t table of 1.990 and a significance of 0.001 0.05, with a regression coefficient of 0.418 and Beta of 0.432 which was the most dominant influence; (2) Work commitment has no significant effect on employee performance with a calculated t value of 1.602 table 1.990 and a significance of 0.113 0.05; (3) Employee attachment has a positive and significant effect on employee performance with a calculated t-value of 2.197 t table of 1.990 and significance 0.031 0.05, with a regression coefficient of 0.288; (4) Simultaneously, leadership style, work commitment, and employee attachment have a significant effect on employee performance with an F value of 61.349 F table 2.72 and a significance of 0.001. A determination coefficient value (R²) of 0.694 indicates that 69.4% of employee performance variations can be explained by all three independent variables, while the remaining 30.6% are explained by other factors outside the study model